Improved methanization and microbial diversity during batch mode cultivation with repetition of substrate addition using defined organic matter and marine sediment inoculum at seawater salinity. (December 2017) - Miura, Toyokazu; Kita, Akihisa; Okamura, Yoshiko; Aki, Tsunehiro; Matsumura, Yukihiko; Tajima, Takahisa; Kato, Junichi; Nakashimada, Yutaka
Highlights: Defined sugar, protein, and fat were methanized at seawater salinity. Batch mode cultivation using marine sediment inocula improved methanization. Substrate-fed and non-fed cultures had distinct microbial community composition. Bacterial members depended on the substrate. The culture of the marine inocula can be used to treat saline waste. Abstract: The activation of microbes, which are needed to initiate continuous methane production, can be accomplished by fed-batch methanization. In the present study, marine sediment inoculum was activated by batch mode methanization with repetition of substrate addition using defined organic matter from sugar, protein, or fat at seawater salinity to investigate the potential for application of the activation method to various types of saline waste and microbial community compositions. All substrates had methane potentials close to the theoretical value except for bovine serum albumin (BSA) whose methane potential was lower, but the maximum methane potential reached the value during repeated methanization. Beta diversity analysis revealed that substrate (especially BSA)-fed and non-fed cultures had distinct microbial community compositions. Bacterial members depended on substrate. Thus, marine sediment inocula activated via the methanization method can be used to effectively treat various types of saline waste.